2018
DOI: 10.1159/000486398
|View full text |Cite
|
Sign up to set email alerts
|

Bardoxolone Methyl Improves Kidney Function in Patients with Chronic Kidney Disease Stage 4 and Type 2 Diabetes: Post-Hoc Analyses from Bardoxolone Methyl Evaluation in Patients with Chronic Kidney Disease and Type 2 Diabetes Study

Abstract: Background: Increases in measured inulin clearance, measured creatinine clearance, and estimated glomerular filtration rate (eGFR) have been observed with bardoxolone methyl in 7 studies enrolling approximately 2,600 patients with type 2 diabetes (T2D) and chronic kidney disease (CKD). The largest of these studies was Bardoxolone Methyl Evaluation in Patients with Chronic Kidney Disease and Type 2 Diabetes (BEACON), a multinational, randomized, double-blind, placebo-controlled phase 3 trial which enrolled pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(77 citation statements)
references
References 17 publications
1
73
0
Order By: Relevance
“…21 Finally, in the BEACON trial, bardoxolone methyl significantly reduced the likelihood of CKD progression, defined as the composite endpoint of end-stage renal disease (dialysis or transplantation) or a 30% or more decline in eGFR. 41 In conclusion, the increase in urinary albumin excretion with bardoxolone methyl treatment was not associated with signs of disease progression or kidney injury, and was likely the result of a pharmacologic effect of improved glomerular filtration and decreased albumin reabsorption. Notably, these effects may preserve kidney function by reducing interstitial inflammation and fibrosis associated with excessive albumin uptake in proximal tubule cells.…”
Section: Discussionmentioning
confidence: 76%
“…21 Finally, in the BEACON trial, bardoxolone methyl significantly reduced the likelihood of CKD progression, defined as the composite endpoint of end-stage renal disease (dialysis or transplantation) or a 30% or more decline in eGFR. 41 In conclusion, the increase in urinary albumin excretion with bardoxolone methyl treatment was not associated with signs of disease progression or kidney injury, and was likely the result of a pharmacologic effect of improved glomerular filtration and decreased albumin reabsorption. Notably, these effects may preserve kidney function by reducing interstitial inflammation and fibrosis associated with excessive albumin uptake in proximal tubule cells.…”
Section: Discussionmentioning
confidence: 76%
“…Nonetheless, Reata Pharmaceuticals reported that post-hoc analysis of the trial data demonstrated preservation of kidney function (55). In addition, preliminary data from the follow-up TSUBAKI study showed improved renal function as assessed by inulin clearance (56).…”
Section: No2-fa Therapy At the Intersection Of Other Successful Pharmmentioning
confidence: 99%
“…We followed up on our observations by using the NRF2 agonist Bardoxolone methyl, which is currently in phase 3 clinical trials for treating chronic kidney disease [62,63]. Interestingly, Bardoxolone methyl impaired the infection.…”
Section: Discussionmentioning
confidence: 99%